THE INFLUENCE OF WOMEN'S TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PRODUCTIVITY IN NON-PROFIT ORGANIZATIONS - Yogi Yunanto; Endang Triwidyati (Media Mahardhika, 2023)
The role of women in public sector jobs is now a universal phenomenon. Based on the multiple linear regression F test, it can be seen that the female transformational leadership style variables together have a significant influence on the work productivity of employees of non-profit organizations with an Fcount value of 17.896> Ftable which is 2.49. This means that the high and low work productivity of employees of non-profit organizations is determined by whether or not the female transformational leadership variable is good. And based on the t test, it is known that only the charisma variable of female transformational leadership partially has a significant dominant influence on the work productivity of employees of non-profit organizations with a calculated t value of 3.265> t table of 2.03. So it can be concluded that the first hypothesis of this study is proven true while the second hypothesis is not proven true.